The Importance of Considering Functional Outcome and Self-awareness in the Assessment of Care Needs: Initial Evaluation of the Brain Injury Needs Indicator. (23rd February 2021) - Copstick, S; Ramos, S D S; Griffiths, T; Wallace, A
Abstract: The relationship between self-awareness (insight) and outcome following acquired brain injury (ABI) is well recognised, but evidence suggests that information regarding brain injury and its cognitive impact is not adequately conveyed to social workers, or appropriately considered when assessing support needs and a person's capacity to make decisions about their care. The Brain Injury Needs Indicator (BINI) provides a solution, by enabling the valid assessment of the needs of those with brain injuries living in a community setting. This paper investigated associations between impaired insight, functional outcome of brain injury, and level of risk, and validated the use of the BINI as an indicator of need. A high prevalence of severe disability (73 per cent) and low insight (30 per cent) was found in a sample of thirty individuals with ABI. The composite BINI score was the measure most strongly related with a clinical assessment of risk ( rs = 0.72, N = 26). Self-report methods may underestimate support needs, especially in those with low levels of insight into their difficulties. The BINI, which combines outcome post-ABI with a measure of insight, provides a more accurate estimate of risk than either measure individually. It is important to include both areas in individual needs assessments.